Environmental determinants of intraspecific variation in five functional traits of Pinus yunnanensis Franch - Song, Xinrui; Liu, Ying; Yu, Dongli; Li, Shuting; Gao, Wuchao; Zeng, Hong; Cao, Dongyu; Zhou, Shixing; Cui, Xinglei (Frontiers in Plant Science, 2024)
Pinus yunnanensis Franch. is a native species in southwestern China, characterized by high polymorphism. However, the environmental drivers of intraspecific variation in its functional traits remain poorly understood. In this study, we examined the relationships between five functional traits (bark thickness, tree height, leaf dry matter content, leaf length, and specific leaf area) and habitat conditions across 20 populations, representing three varieties: var. yunnanensis (the original variety), var. pygmaea, and var. tenuifolia. Our experiments aimed to determine whether the functional traits varied among the three varieties under different environmental conditions. As specific leaf area and leaf dry matter content showed no significant correlations with any environmental factors, we focused our analysis on the remaining three traits. Using random forest models, we assessed the significance of each environmental factor and found the following: Temperature seasonality was a key determinant of tree height; soil particle size (clay and sand) had the strongest influence on bark thickness; and for leaf length, precipitation during the driest quarter was the most important factor. These findings offer insights into the variation in functional traits of P. yunnanensis and enhance our understanding of its adaptation to diverse environments.